Physical, Cognitive, and Psychosocial Characteristics Associated With Mortality in Chronic TBI Survivors: A National Institute on Disability, Independent Living, and Rehabilitation Research Traumatic Brain Injury Model Systems Study. Issue 4 (July 2018) - O'Neil-Pirozzi, Therese M.; Ketchum, Jessica M.; Hammond, Flora M.; Philippus, Angela; Weber, Erica; Dams-O'Connor, Kristen
Abstract : Objective: To compare a group of individuals who died more than 1 year posttraumatic brain injury (TBI) with a matched group of survivors and to identify physical function, cognitive function, and/or psychosocial function variables associated with mortality. Design: Secondary analysis of data from a multicenter longitudinal cohort study. Setting: Acute inpatient rehabilitation facilities and community follow-up. Participants: Individuals 16 years and older with a primary diagnosis of TBI. Main Outcome Measures: Functional Independence Measure (FIM), Disability Rating Scale, Participation Assessment with Recombined Tools Objective, Extended Glasgow Outcome Scale, Satisfaction With Life Scale. Results: Individuals who died were distinguishable from their surviving counterparts. They demonstrated significantly poorer global functioning on all physical, cognitive, and psychosocial functioning variables at their most recent study follow-up visit prior to death. FIM Motor demonstrated the largest difference between survival groups, suggesting that independence in mobility may be particularly indicative of likelihood of longer-term survival. Conclusions: These findings may inform continued research to elucidate functional characteristics of individuals postchronic TBI prior to their death and to identify opportunities for prevention of accelerated death and interventions to improve health, longevity, and quality of life.